Social Rehabilitation Management Drug Abusers - Apollo Sinambela (Journal of Social Science, 2023)
The objective of the research is to understand the management of social rehabilitation of narcotics and drug abusers in BNN Rehabilitation Center Lido, Bogor. Other objective is to determine any obstacles in the social rehabilitation, to determine the skills development officer social rehabilitation and to determine the results/achievement of social rehabilitation. The research uses a qualitative approach. The research method is case study. The research results show: (1) In the area of management of social rehabilitation, Babesrehab BNN applied: (a) the planning of social rehabilitation run in an integrated, ranging from human resource, selection of methods/approaches and rehabilitation activities, placement, selecting counselors; (a) to achieve the goals and realize social rehabilitation plan, then designed an organizational structure, allocated tasks to be executed according to the parts contained in the umbrella organization of large social rehabilitation; (a) social rehabilitation supervision intended to keep the goal of social rehabilitation remains on the corridor; (d) the implementation of social rehabilitation implemented in every phase, from primary to re-entry; and (e) supervision in the field of social rehabilitation delegated to other persons who are authorized to perform the supervision, not by the head of departement or division; (2) the obstacle of social rehabilitation ranging from HR, resident, organization communication, and society; (3) the effort of social rehabilitation to increase HR competency based on education, workshop, seminar, and on job training; and (4) achievement of social rehabilition marked by an indicator that resident could reach normal lives without relapsed addiction.